Evaluation of dietary supplementation of frankincense oil on broiler chicken growth performance, hepatic histomorphology, antioxidant activity, blood biochemical parameters, and inflammatory responses - Shimaa A. Amer; Amany Behairy; Ghada I. Abd El-Rahman; Ahmed Gouda; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Amr A. Moustafa; Hebatallah Abdel Moniem; Simon J. Davies; Asmaa EL-Sayed Kamel (Italian Journal of Animal Science)
This investigation aimed to assess the potential impact of frankincense oil (FKO) from Boswellia serrata on broiler chicken growth performance parameters, including body weight (BW), body weight gain (BWG), feed intake (FI), and feed conversion ratio (FCR) during the starter, grower, and finisher phases. We also evaluated the hepatic histology, serum hepatorenal function tests, antioxidant activity, and inflammatory responses. A total of 400 three-day-old male chicks (Ross 308 broiler) (100.40 ± 0.13 g) were randomly assigned to four treatment groups (10 replicates/group, ten chicks/replicate). The birds were fed basal diet (FKO0, control group) or basal diet supplemented with 200, 400, and 600 FKO/kg of diet (FKO200, FKO400, FKO600, respectively). The experiment lasted 35 days. Gas chromatography-mass spectrometry analysis revealed that FKO contained 36 constituents, with the dominant compounds being 1,6,10-DODECATRIEN-3-OL, 3,7,11-TRIMETHYL-, [S-(Z)]- (12.42%), ç-Elemene (12.42%), à-Farnesene (12.42%), PHENOL and 2,4-BIS(1,1-DIMETHYLETHYL)- (7.15%). Distinctive FKO levels (200-600 mg/kg) showed greater BW without influencing total feed intake compared to the FKO0 treatment. The FCR was improved by the addition of FKO to the diets. The blood concentrations of alanine aminotransferase and creatinine increased (p < 0.05) in the FKO600 treatment. Dietary FKO linearly lowered serum malondialdehyde levels and enhanced blood total antioxidant capacity, catalase, superoxide dismutase, and pro-inflammatory cytokines (interleukine-1 β and interferon γ) compared to the control group. Broilers fed FKO at levels 200–600 mg kg−1 diet also exhibited lower serum total cholesterol, triglyceride, and low-density lipoprotein cholesterol levels. Furthermore, the FKO400 and FKO600 treatments showed an increase in high-density lipoprotein cholesterol (p < 0.01). Histomorphological analysis of the liver indicated no significant differences between the FKO-supplemented groups and the control group. However, the immunoexpression of the pro-inflammatory cytokine (transforming growth factor β) was considerably increased in the liver and spleen tissues of birds fed FKO in a level-dependent manner. In conclusion, dietary supplementation of FKO at levels up to 600 mg/kg can serve as a natural growth promoter in broiler chickens, leading to enhanced growth, hypolipidemic properties, antioxidant status, and immune responses.